CTIM-27. LOCOREGIONAL B7-H3-SPECIFIC CAR T CELLS FOR CHILDREN AND YOUNG ADULTS WITH DIPG: INTERIM REPORT OF BRAINCHILD-03 ARM C. (12th November 2021) - Vitanza, Nicholas; Wilson, Ashley; Yokoyama, Jason; Johnson, Adam; Gust, Jule; Huang, Wenjun; Albert, Catherine; Pinto, Navin; Foster, Jessica; Orentas, Rimas; Paulovich, Amanda; Berens, Michael; et al.
Abstract: Following preclinical optimization of B7-H3-specific CAR T cells against pediatric brain tumor models, we opened BrainChild-03 (NCT04185038), a phase 1 clinical trial of repeatedly dosed, outpatient, locoregional B7-H3-specific CAR T cells for children with recurrent/refractory central nervous system (CNS) tumors or diffuse intrinsic pontine glioma (DIPG). Here, we report the interim findings from patients enrolled on Arm C, dedicated to DIPG. The primary endpoints are feasibility and safety, with secondary endpoints of disease response. We utilize second-generation CAR T cells with a 4-1BB costimulatory domain and a methotrexate-resistant human DHFR mutein (huDHFR FS ; L22F, F31S), allowing for methotrexate selection. We do not deliver conditioning chemotherapy. The first three evaluable patients with DIPG all met feasibility for generating a balanced CD4:CD8 CAR T cell product, with 3.85x10 9 CAR T cells generated for S005, 4.29x10 9 for S008, and 2.45x10 9 for S012, allowing for greater than 6 months of biweekly dosing for each patient. All subjects were treated at Dose Level 1 (1x10 7 CAR T cells). S005 received 10 doses before clinical progression greater than 2 years from diagnosis, S008 has received 10 doses and continues on therapy with decreased tumor volume, and S012 has received 5 doses and continues on study with stable disease. There have been no dose limiting toxicities (DLT). 3/3 patients exhibited post infusion fever, headache, and elevated serum CRP but no evidence of cytokine release syndrome (CRS) or systemic CAR T cells. 0/3 patients required PICU admissions. In the cerebrospinal fluid (CSF), 2/3 patients have had elevations of cytokines such as CXCL10 and CCL2, as well as circulating CSF CAR T cells. Advanced serial patient CSF proteomic and transcriptomic profiling are underway. Ultimately, this report provides preliminary evidence that outpatient locoregional B7-H3 CAR T cells for children with DIPG may be feasible and tolerable.